Application and training of Al-Fashdu therapy for healing and reducing the use of chemical drugs - Anindya Prastiwi Setiawati; Masliyah Masliyah; Eva Sundari (University of Merdeka Malang, 2023)
Al-Fashdu therapy is an Islamic-based alternative treatment that is one of the community's options for dealing with health problems. In addition to reducing disease, this therapy is inexpensive because it does not use chemical drugs. This Community Service aims to introduce treatment using the Al-Fashdu method to residents of RT 06 RW 05, Perum Lembah Harapan, Lidah Wetan Village, Lakarsantri District, Surabaya City. Residents of RT 06 mostly complain of various illnesses and have to consume a lot of chemical drugs, but chemical drugs also cause complaints of pain in other body organs. The method of implementing this community service program uses application, training, and assistance on how to do Al-Fasdhu therapy. The training was attended by more than 75 partners, with an average age of 50 years and over. After being treated with Al-Fashdu therapy, the next activity is to provide Al-Fashdu therapy training to the community with the aim of being able to carry out Al-Fashdu therapy independently. As a result of this community service activity, many residents feel their bodies are healthier and are able to independently apply Al-Fashdu therapy.